Serum sensitivity of a Pseudomonas aeruginosa mucoid strain. - Schiller, N L (1984)
The susceptibility of Pseudomonas aeruginosa 144M (a mucoid strain isolated from the sputum of a cystic fibrosis patient) to the bactericidal activity of pooled fresh normal human serum (FHS) was examined. FHS at concentrations of greater than or equal to 2.5% was capable of killing greater than 95% of strain 144M. Strain 144M was killed by FHS in a dose-dependent manner. Although either immunoglobulin M (IgM) or IgG was bactericidal in the presence of complement, IgM was about 10 times as effective as IgG. However, optimal killing activity required both IgM and IgG and complement, activated by the classical pathway. A role for lysozyme in the killing of 144M was demonstrated only when low concentrations of FHS were used. In contrast to 144M, P. aeruginosa strains 144NM and 144M(SR) were totally resistant to FHS at all of the concentrations tested (up to 50%). Neither the FHS susceptibility of 144M nor the FHS resistance of 144NM or 144M(SR) was altered by choice of growth medium, growth phase, or temperature of growth. Results of absorption studies with whole organisms, isolated outer membrane preparations, or lipopolysaccharide (LPS) from each strain suggest that the antigen(s) which binds the bactericidal immunoglobulins is accessible on the surface of 144M but not on the surface of 144NM or 144M(SR), is insensitive to trypsin treatment, and is believed to be LPS. Sodium dodecyl sulfate-polyacrylamide gel electrophoresis of the three LPS preparations demonstrated that 144M LPS contained primarily lipid-A-core polysaccharide components, whereas the LPS from 144NM and 144M(SR) were heterogeneous, with various degrees of O-side-chain substitution. These results suggest that at least one target for bactericidal antibody on the surface of 144M is contained in the rough LPS of this strain.